ANALISIS DAN PERANCANGAN APLIKASI GPS BERBASIS ANDROID UNTUK CV. EXPRESS TRI’YO MUJUR - Lony Sutrisno (Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
We are all aware of the rapid development of information technology today. The development of information technology we can feel Start of various activities in their daily lives, including in drive activity. Where the drive will be now easier with the navigation application. Android, as a system, is a Java-based operating system that runs on the Linux 2.6 kernel. Android applications are developed using Java and easy to adjust to a new platform (DiMarzio, 2008). Android is a complete collection of software that can be an operating system, middleware, and key applications of mobile devices. Android consists of a complete stack, starting from the boot loader, device driver, and library functions, until a software API.The authors collected data in this study using observations regarding some existing navigation applications in and compared with the needs of the market are still required User. Any application that has been built and certainly has its drawbacks the advantages of each. Including the GPS application of this extreme.The drawback there is the framework used is hybrid thus making the performance of the application is to be reduced. While the advantages are no navigation application has pick me up features. Conclusions from this research is the application is very helpful for facilitate users in driving because of the navigation features and other additional unique features. Keywords: analysis and system design, android, navigation, ionic framework